The Effect of HIIT on Increasing VO2 Max in White Water Rafting Athletes - Hadiono Hadiono; Nuril Huda; Andes Permadi; Ajeng Nur Khoirunnisa; Mirna Larasati (UNIB Press, 2024)
This research was carried out to find out the effect of training using the High Intensity Interval Training (HIIT) model on increasing VO2 Max in white water rafting athletes. This research design is an experimental pre-post design. This research used 28 white water rafting athletes, consisting of 16 male athletes and 12 female athletes. The athlete's age range is 16-22 years. All research subjects were in healthy condition. All subjects were given the same treatment, namely training using the HIIT model. Intervention with HIIT cardio training. The HIIT training model uses an intensity of 90-100% of Maximal Heart Rate (MHR). HIIT is done with a ratio of 30 seconds of exercise then 3 minutes of rest. Exercise uses an intensity of 90% MHR in the first week and will be increased every week until it reaches 100% MHR. Exercises were carried out for 6 weeks with a frequency of 4x per week. VO2 Max measurements are carried out using a multistage test instrument. In this research, it can be seen that HIIT exercise carried out for 6 weeks with a frequency of 4 times per week can increase athletes' VO2 Max. There is a significant difference in VO2 Max between male and female athletes with a difference test result of P < 0.05. Exercise using the HIIT model which is carried out for 6 weeks with a frequency of 4x a week can increase the VO2 Max of white water rafting athletes. HIIT training can be used as a recommendation to increase VO2 Max for white water rafting athletes.